2016
DOI: 10.12657/denbio.076.014
|View full text |Cite
|
Sign up to set email alerts
|

Changes in elm (Ulmus) populations of mid-western Poland during the past 35 years

Abstract: Three elm species are native to Poland: wych elm (Scots elm) (Ulmus glabra Huds.), field elm (U. minor Mill.), and European white elm (fluttering elm) (U. laevis Pall.). The epidemic of Dutch elm disease (DED) has led to a decrease in the popularity of elm cultivation. An analysis of forestry data was the first step in the assessment of elm resources. The area of forest stands where elms are dominant has more than doubled since 1978. Lowland alluvial forests rank first in regards to the number of elm localitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 19 publications
2
25
1
Order By: Relevance
“…Our observations confirm the previous data from Poland (Mańka et al, 1978) that U. minor is the most sever damaged by DED and the less U. laevis. Although in our study the number of isolates received from U. leavis was the highest, however, field studies suggest that this species prevails in the elm resources in Poland (Danielewicz, 2008;Filipiak & Napierała-Filipiak, 2015;Napierała-Filipiak et al, 2016). Data provided by Peterken & Mountford (1998) or Oheimb & Brunet (2007) showed that DED was able to decrease the elm population but very rarely cause the total elimination of this tree species.…”
Section: Resultscontrasting
confidence: 51%
“…Our observations confirm the previous data from Poland (Mańka et al, 1978) that U. minor is the most sever damaged by DED and the less U. laevis. Although in our study the number of isolates received from U. leavis was the highest, however, field studies suggest that this species prevails in the elm resources in Poland (Danielewicz, 2008;Filipiak & Napierała-Filipiak, 2015;Napierała-Filipiak et al, 2016). Data provided by Peterken & Mountford (1998) or Oheimb & Brunet (2007) showed that DED was able to decrease the elm population but very rarely cause the total elimination of this tree species.…”
Section: Resultscontrasting
confidence: 51%
“…Published data indicated that in comparison with the 1970s, the number of forest stands dominated by elms has increased [25,30]. The percentage of localities with DED symptoms in individual forest regions is very similar (Figure 3, Table 3d).…”
Section: Discussionmentioning
confidence: 82%
“…C. Moreau), entered Britain on imported logs and killed c . 30% of elms between 1920 and 1940 (Napierała‐Filipiak et al., ). Similar losses were reported across Europe with even heavier losses in North America.…”
Section: Herbivory and Diseasementioning
confidence: 99%
“…Ulmus glabra has been less affected than suckering elms (Cogolludo‐Agustín, Agúndez, & Gil, ) and is now the most numerous elm in central and eastern Europe. But U. glabra is by no means immune and indeed is more susceptible to the DED fungus than U. minor or U. laevis (Napierała‐Filipiak et al., ; Pinon et al., ). In 4‐year‐old (3–4 m high) U. glabra in the Czech Republic inoculated with O. novo‐ulmi , sap flow was reduced 10 days after inoculation and total occlusion of xylem stopped sap flow after 11–16 days (Urban & Dvořák, , ).…”
Section: Herbivory and Diseasementioning
confidence: 99%